AZA Corporation - Mhd Nasir, Mohamad Zool Ekhsan; Narasid, Muhammad Adnin; Abdul Rashid, Muhamad Adib Adham (2019)
Our company name is AZA Corporation. AZA is based on our partnership first alphabets names. It was intended to commercialize our product to be the best Smart Rubbish Compress (S.R.C) because our product is have automatic compress, anti-smelly and watery removal, can hold more garbage, easy and safe trash removal, appropriate at any places, sensor and high durability. Our company want to make our product be the highest demand among the other product.